Differential Adaptation Strategies by Agro-Ecological Zones in African Livestock Management - Seo, S. Niggol; Mendelsohn, Robert; Dinar, Ariel; Kurukulasuriya, Pradeep (World Bank, Washington, DC, 2012)
This paper examines how farmers have adapted their livestock operation to the current climate in each agro-ecological zone in Africa. The authors examine how climate has affected the farmer's choice to raise livestock or not and the choice of animal species. To measure adaptation, the analysis regresses the farmer's choice on climate, soil, water flow, and socio-economic variables. The findings show that climate does in fact affect the farmer's decision about whether to raise livestock and the species. The paper also simulates how future climates may alter these decisions using forecasts from climate models and the estimated model. With a hot dry scenario, livestock ownership will increase slightly across all of Africa, but especially in West Africa and high elevation agro-ecological zones. Dairy cattle will decrease in semi-arid regions, sheep will increase in the lowlands, and chickens will increase at high elevations. With a mild and wet scenario, however, livestock adoption will fall dramatically in lowland and high latitude moist agro-ecological zones. Beef cattle will increase and sheep will fall in dry zones, dairy cattle will fall precipitously and goats will rise in moist zones, and chickens will increase at high elevations but fall at mid elevations. Livestock adaptations depend on the climate scenario and will vary across the landscape. Agro-ecological zones are a useful way to capture how these changes differ from place to place.